Marketing Analysis of Lemongrass (Cymbopogon citratus) in Cialam Jaya Village, South Konawe District - Muliani, Waode Sri; Surni, Surni; Hidrawati, Hidrawati (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2023)
Costs of marketing and the length of marketing channels will influence the marketing margin. This research aims to determine the marketing channels for lemongrass, marketing margins, and efficiency of the marketing channels for lemongrass. A quantitative descriptive approach with marketing margin analysis was used to measure marketing margins and efficiency. The research results show that the marketing channels for lemongrass are Producers, Wholesalers, Retailers, Consumers, and Producers, Collectors, Wholesalers, Retailers, and Consumers. The performance of the lemongrass marketing channel in Marketing Channel I is a marketing margin of IDR 4,000/Kg and IDR 3,000/Kg with a marketing profit of IDR 3,083/Kg and IDR 2,432/Kg, while in Marketing Channel II the marketing margin is IDR 2,000/Kg, IDR 2,000/Kg and IDR 3,000/Kg with marketing profits of IDR 1,130/Kg, IDR 1,348/Kg and IDR 2,558/Kg. The results of the analysis show that the percentage of price share received by producers (Famer's Share) from the two marketing channels each shows above 50%, which means that both marketing channels are efficient.